Keeping secrets - Martin, Ann M., 1955-; Andreasen, Dan (New York : Scholastic, 2009)
Flora, Ruby, Olivia, and Nikki have a new neighbor, Willow, who seems like a natural fit for their group of friends. But Willow doesn't seem to want to be friends, maybe because she has a secret.
5.
009-up.
Keywords: Secrecy -- Juvenile fiction; Friendship -- Juvenile fiction